A qualitative study of patient experience of an open fracture of the lower limb during acute care - Tutton, E; Achten, J; Lamb, S; Willett, K; Costa, M (British Editorial Society of Bone and Joint Surgery, 2018)
Aims The aim of this study was to explore the patients’ experience of recovery from open fracture of the lower limb in acute care. Patients and Methods A purposeful sample of 20 participants with a mean age of 40 years (20 to 82) (16 males, four females) were interviewed a mean of 12 days (five to 35) after their first surgical intervention took place between July 2012 and July 2013 in two National Health Service (NHS) trusts in England, United Kingdom. The qualitative interviews drew on phenomenology and analysis identified codes, which were drawn together into categories and themes. Results The findings identify the vulnerability of the patients expressed through three themes; being emotionally fragile, being injured and living with injury. The participants felt a closeness to death and continued uncertainty regarding loss of their limb. They experienced strong emotions while also trying to contain their emotions for the benefit of others. Their sense of self changed as they became a person with visible wounds, needed intimate help, and endured pain. When ready, they imagined what it would be like to live with injury. Conclusion Recovery activities require an increased focus on emotional wellbeing. Surgeons are aware of the need for clinical expertise and for adequate pain relief but may not be as aware that their patients require support regarding their body image and help to imagine their future life.